Guatemala Art Exhibit
Actual year not provided. Video made digital in 2010. Guatemala Oct 30th – 31st Film Summary Film Duration - 12:22 Denise Lugo behind camera Starts with viewing of Dresses (Guatemalan?) being set up for exhibition 2 men and a woman discuss in Spanish while looking through a book Video shows paintings on display, mostly of women and children. 2 women discussing in Spanish Items being unloaded and photographs/paintings being hung for display Outside view of gallery space. "Día de los Santos/ Día de los Muertos" on a banner being hung. Banner with Guatemalan mural being hung as well. Women putting decals of quotes on wall. Shots of installation plots and flower arrangements in room of gallery More shots of women continuing to put decals of quotes on wall of gallery Mission Statement of the gallery is shown, a little unreadable Shots of the hung show and installation